2012
DOI: 10.1063/1.4752477
|View full text |Cite
|
Sign up to set email alerts
|

Periodic dripping dynamics in a co-flowing liquid-liquid system

Abstract: Periodic dripping into air (the “leaky faucet” phenomenon) is now known and understood in detail, while the same problem for fluids dispersed into a second co-flowing immiscible liquid has received far less attention. Depending on the excitation mode of the fluid phases, distinctive oscillations in the dispersed fluid column lead to the formation of droplet groups. In this work, the impact of the velocity of the continuous phase, volume flow rate of the disperse phase, superimposed pressure oscillations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…[22] Theoretical analysis and numerical simulations have been carried out to describe qualitatively and quantitatively the features of the droplet detachment from a needle's tip. [23][24][25] The present study also raised interesting scientific issues such as the fluids interactions between dropping liquid metal and the base cooling fluid as well as the practical strategies to precisely control the deposition quality of the final metal objects in liquid phase.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[22] Theoretical analysis and numerical simulations have been carried out to describe qualitatively and quantitatively the features of the droplet detachment from a needle's tip. [23][24][25] The present study also raised interesting scientific issues such as the fluids interactions between dropping liquid metal and the base cooling fluid as well as the practical strategies to precisely control the deposition quality of the final metal objects in liquid phase.…”
Section: Introductionmentioning
confidence: 92%
“…Over the years, there have been a lot of experimental and dynamic researches on the principle of the drop formation at a capillary tip. [21][22][23] When the liquid metal is injected into another immiscible fluid via the needle, two drop formation mechanisms will be observed. If the injection velocity of the liquid metal is lower than a certain critical value, the drops will be formed directly at the needle tip.…”
Section: Introductionmentioning
confidence: 99%
“…However, no extensive effect of dispersed or continuous phase flow rates on polydispersity was presented. Cramer et al (2012) studied the polydispersity in droplet trains formed in dripping mode using a co-flow approach. Cordero et al (2011) investigated the co-flow approach for drop formation and found that the polydispersity decreased with increasing dispersed phase flow rate in the jetting regime.…”
Section: Introductionmentioning
confidence: 99%
“…The coaxial microchannels are nested structures, i.e., the inner tube opens into the dispersed phase and the outer annular tube opens into the continuous phase. The continuous phase and the dispersed phase flow in the same direction and meet at the orifice of the inner tube [19,21,[24][25][26][27]. The dimensionless numbers, such as the capillary number Ca c = η c u c /σ of the continuous phase, the Weber number We d = ρ d u 2 d D d /σ of the dispersed phase, the Reynolds number Re d = ρ d u d D d /η d of the dispersed phase, and the ratio of the two-phase flow rates Q d /Q c , are generally used to describe these physical systems.…”
Section: Introductionmentioning
confidence: 99%